Investigation Action Criminal Circulation Cosmetics Illegal - Ayu Ma'rifa, Andi Jessica; Mappaselleng, Nurfadhilah; Zulkifli Muhdar, Muhammad (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to find out and explain the process of investigating illegal cosmetics distribution crimes in Makassar and to find out and explain the factors that influence the investigation of illegal cosmetics distribution crimes in Makassar. This study uses an empirical legal method with a qualitative descriptive approach. Data were obtained through interviews and data collection with law enforcement officers. The results of this study indicate that the process of investigating illegal cosmetics distribution crimes in Makassar by the South Sulawesi Regional Police is basically carried out in accordance with the provisions of the applicable Criminal Procedure Code (KUHAP). The factors that hinder the process of investigating illegal cosmetics distribution crimes in Makassar. This research recommendation requires and is important to have a more efficient coordination system between police investigators and BPOM officers to facilitate the investigation process until the determination of suspects